PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN TERHADAP KOMPETENSI DIGITAL GURU DI SMKN KOTA PADANG - Faras Abiyu; Tia Ayu Ningrum; Novriyanti Achyar; Merika Setiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the use of Artificial Intelligence (AI) in learning on teachers' digital competence at State Vocational High Schools (SMKN) in Padang City. This study employed a quantitative approach with a descriptive correlational method involving 253 teachers selected through the Proportional Random Sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics and simple linear regression. The results indicate that both the use of Artificial Intelligence (AI) in learning and teachers' digital competence are in the good category. Furthermore, the use of Artificial Intelligence (AI) in learning has a positive and significant effect on teachers' digital competence, contributing 20.4% to its improvement. These findings suggest that optimizing the use of AI can enhance teachers' digital competence. Therefore, training and mentoring programs on the use of AI are needed to support teachers in improving learning practices in the era of digital transformation.